Real Responses to Anti-Tax Avoidance: Evidence from the UK Worldwide Debt Cap - Katarzyna Anna Bilicka; Yaxuan Qi; Jing Xing (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We analyze how multinational firms reallocate real operations and debt across their affiliates in response to anti-tax avoidance policies. The UK introduced a worldwide debt cap in 2010, generating a quasi-natural experiment that limited interest deductibility for a group of multinational firms. We find that multinationals affected by the reform reduced the amount of debt held in the UK and increased debt held abroad. Affected multinationals reallocated a share of their real operations away from the UK. Our findings provide causal evidence for tax-motivated debt and real activity reallocation within multinationals and show how multinationals can circumvent tax avoidance regulations.
Keywords: H25; H26; 330; debt shifting; multinational companies; capital reallocation